Control of wind power supply systems - Tay, Wee Boon. (2010)
Actual strategies for sustainable energy development have as prior objective the gradual replacement of fossil-fuel-based energy sources by renewable energy ones. Among the clean energy sources, wind energy conversion systems currently carry significant weight in many developed countries. Following continual efforts of the international research community, a mature wind energy conversion technology is now available to sustain the rapid dynamics of concerned investment programs.